Caracterización quimica de los flavonoides presentes en Ficus citrifolia Mill - Garcia Alvarado, Katic Tamiana (2015)
Ficus citrifolia Mill. belong to the family Moraceae; is a native Ecuadorian plant and it is widely distributed in the territory. This species is used in the shuar traditional medicine as anti-inflammatory and healing. Previous phytochemical research have determined the presence of flavonoids and high antioxidant activity in this plant, being this the reason of this study which objective is the chemical characterization of flavonoids that are found in the rates of 80% in the alcoholic extract of Ficus citrifolia found through chromatography techniques: thin-layer chromatography (TLC) and high-performance liquid chromatography with diode array (HPLC-DAD). Thin-layer chromatography (TLC) showed seven moieties of the sample of Ficus citrifolia Mill. that are flavonoids, the values of Rf were calculate for the moieties and standards of flavonoids. Also was shown a great antioxidant capacity for the third and fourth moieties through the autobiography TLC with ethanolic solution 0,5% of 2,2-diphenyl-1-picrylhydrazyl (DPPH). Through HPLC-DAD the values that were obtained retention time (min) and absorption maximum peak (nm) for the moieties of the samples and the standards of flavonoids coincidence were obtained for the first, second and sixth fraction. With the analysis of the results it was identified the presence of rutin (first moiety – Rf 1), hyperoside (second moiety – Rf 2) and luteolin (sixth moiety – Rf 6) in the extract of Ficus citrifolia reassuring with it its anti-inflammatory potential.